2006
DOI: 10.1002/pssb.200541356
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of ScSb, ScAs, ScP and ScN

Abstract: The structural and electronic properties of ScSb, ScAs, ScP and ScN III -V materials are investigated within a version of the first-principles full potential linear muffin-tin orbitals method (FPLMTO) that enables an accurate treatment of the interstitial regions. At high pressure, the transition from rocksalt (B1) to CsCl (B2) structure is found to be possible. The zinc blende phase is also investigated and is found to give a semiconductor behavior with a wide bandgap to all our materials. The latter is direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
25
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 13 publications
(25 reference statements)
12
25
1
Order By: Relevance
“…at T=0 K. In figure 3, the difference between the enthalpy of the CsCl and RS structures (∆H CsCl−RS ) decreases to zero at the transition pressure of 285.2 GPa. The present transition pressure is found to be smaller than the ones (341 GPa [9], 332.75 GPa [11]) calculated directly from the slope of the common tangent.…”
Section: Methods Of Calculationscontrasting
confidence: 77%
See 1 more Smart Citation
“…at T=0 K. In figure 3, the difference between the enthalpy of the CsCl and RS structures (∆H CsCl−RS ) decreases to zero at the transition pressure of 285.2 GPa. The present transition pressure is found to be smaller than the ones (341 GPa [9], 332.75 GPa [11]) calculated directly from the slope of the common tangent.…”
Section: Methods Of Calculationscontrasting
confidence: 77%
“…35 and 195.95 GPa found for RS-ScN within EV ex -PW co -GGA and PBE-GGA's, respectively, are the best ones providing the measured value of 182∓40 GPa [1]. The present bulk moduli of EV ex -PW co -GGA and PBE-GGA's are also found to be in the range of 196-202 GPa defined by the corresponding results of ab-initio PP and FP-LAPW calculations within PBE-GGA and PCVJPSF-GGA [9,11] and PBE-GGA [9,10] at the cross point. Therefore, the necessary pressure providing the transition from RS to CsCl corresponds to the zero difference between the enthalpy of the structures.…”
Section: Methods Of Calculationsmentioning
confidence: 64%
“…The ground-state properties of ScN have been investigated by Takauchi [5] using fullpotential linearized augmented plane wave calculations that revealed that NaCl structure is the most stable one in the ground state with almost zero indirect bandgap. Recently, the ground-state properties and high-pressure structural phase transition (B 1 -B 2 ) of ScX (X ¼ N, P, As, Sb) compounds have been studied by Maachou et al [6] and Tebboune et al [1], emphasizing the metallic behavior of these compounds. Bouhemadou and Khenata [7] have studied the structural stability and elastic properties of ScSb and YSb under pressure using a full-potential augmented plane-wave (PW) plus local orbitals (FP-APWC þ lo) method.…”
mentioning
confidence: 99%
“…The structural, optical, magnetic, and electronic properties of scandium pnictides have been studied both experimentally and theoretically [1][2][3][4][5][6][7][8][9][10]. From the point of view of theoretical studies it, however, remained controversial as to whether ScN along with its other members in the Sc-pnictogen series is metallic or a semiconductor [1].…”
mentioning
confidence: 99%
“…No significant differences in contrast in the STEM images can be seen between the regions with cubic stacking (these are effectively one large stacking fault) and the rest of the material, indicating minimal compositional differences. However, the zinc blende phase of GaN has a band gap approximately 0.2 eV lower than that of hexagonal GaN 25,26 , and the band gap of zinc-blende ScN is expected to be lower than that of zinc-blende GaN 27 , such that the band gap of the inclusions should decrease with increasing Sc content. Therefore, we conclude that inclusions of the zinc blende phase are the cause of the apparent reduction in band gap with increasing Sc content.…”
mentioning
confidence: 99%